Estimating genetic diversity, mating system and pollen dispersal to inform ex situ conservation of the tree Genipa americana L. - Melo, Marília Freitas De Vasconcelos; Sebbenn, Alexandre Magno; Rossini, Bruno Cesar [UNESP]; Muniz, Ana Veruska Cruz Da Silva; Rodrigues, Carlos Jose; Marino, Celso Luis [UNESP]; Moraes, Mario Luiz Teixeira De [UNESP] (Cambridge University Press (CUP), 2021)
Using microsatellite loci, we assessed the mating system and genetic diversity of the dioecious tropical tree Genipa americana in a natural population (NP) and a progeny test (PT). For NP, we also estimated the paternity correlation within and among fruits and mean pollen dispersal distance. As expected for dioecious species, all offspring originated from outcrossing (t = 1). Mating among relatives (1-ts) and paternity correlation (rp) were variable among progenies (1-ts = 0.03-0.19; rp = 0.04-0.40), but greater in NP than in PT. Fixation index (F) was generally significant and lower in adults than in offspring, indicating selection against inbred individuals. Paternity correlation was higher within (0.40) than among (0.26) fruits, indicating a lower effective number of pollen donors (Nep) within (2.5) than among (3.8) fruits. Due to the higher rp in NP, the effective size within progenies (Ne) was lower (2.69) than PT (3.27). The pollen dispersal pattern was strongly leptokurtic, suggesting long-distance pollen dispersal (mean of 179 m). The results show that both populations can be used for seed collection in environmental reforestation programmes; however, considering that PT is structured in maternal progenies, NP is more suitable for seed collection due to the lower probability of mating among related trees.
Keywords: conservation genetics; gene flow; microsatellite loci; progeny test; tropical trees